Synthesis and Luminescence Properties of β-NaGdF4:Yb3+, Er3+ Nanoparticles. Issue 1 (May 2021) - Zhang, Cong; Yang, Ju; Cui, Wenzhe; Ren, Guozhong
Abstract: Ln (Yb 3+ Er 3+ )-doped NaGdF4 nanoparticles were prepared by a hydrothermal method. The structure and composition of the samples as prepared nanomaterials were characterized by XRD, TEM, and UV-visible absorption-spectrum analysis. Based on further analysis results that are rarely reported, the cyclohexane solution sample shows peak at 376, 520 and 653nm. The transmitted spectrum indicated that all samples present the pure hexagonal phase with nanorods microstructure. It was found that the Gd ions' doping percentage from 73% to 93% is more beneficial to glow. The synthesis steps of the hydrothermal method are simple and the particles synthesized by this method showed uniform size, table structure and good dispersion. The lanthanide fluoride nanocrystals prepared in this experiment can be used as an excellent optical material. The samples were then irradiated by laser 980 nm at room temperature, and they emitted bright and unusually stable upconvert visible light. Experiments have shown that NaGdF4 (Yb 3+ Er 3+ ) can present good up-conversion luminescence. Therefore, it provides us with more possibilities in application fields such as probes, scanning and display.